The Relationship Between Knowledge of Mother and Family Support with Immunization Status Td in Sub PIN Difteri - Ishmatul Fajriyah (Universitas Airlangga, 2014)
The number of diphtheria cases in East Java has been increasing every year. Surabaya City is one of the cities implementing the Diphtheria Sub National Immunization Week (Sub PIN) program. Coverage of Diphtheria Sub PIN for children aged more than 7-15 years at the Public health center (PHC) of Kalijudan is only 79.15%, while the minimum target set is 95%. This study was conducted to determine the relationship between knowledge and family support with Tetanus diphtheria immunization (Td) in the Sub-PIN program. The study was conducted with a case-control design using a quantitative approach. The case population was all children aged more than 7-15 years in the working area of the PHC of Kalijudan whose Td immunization status in Sub PIN was incomplete. The number of respondents was 60 people. Sample selection with simple random sampling. The variables studied were characteristics, mother's knowledge, and family support. The results showed that the majority of respondents had a low level of knowledge (55%) about Diphtheria Sub PIN and diphtheria. Chi-square test showed that there was a relationship between maternal knowledge level and Td immunization status in diphtheria sub PIN (p = 0.038). There was a relationship between family support and Td immunization status in diphtheria sub PIN (p = 0.030). It is expected that cross-sector cooperation in the implementation of diphtheria sub PIN and increases maternal knowledge related to diphtheria sub PIN and diphtheria disease by counseling.